2016
DOI: 10.3354/meps11605
|View full text |Cite
|
Sign up to set email alerts
|

Symbiont carbon and nitrogen assimilation in the Cassiopea–Symbiodinium mutualism

Abstract: Symbiotic interactions in the marine environment have long been represented by mutualisms between photosymbionts and benthic marine invertebrates like corals and sponges. Although 'upside-down' epibenthic jellyfish in the genus Cassiopea also derive a substantial metabolic benefit from abundant communities of the dinoflagellate symbiont Symbiodinium, comparatively little is known about the efficiency of carbon (C) and nitrogen (N) assimilation within the Cassiopea holobiont. Using standardized 6 h incubations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 25 publications
3
40
0
Order By: Relevance
“…These experiments showed that labeled glycerol disappeared in <30 min, likely through utilization in lipid synthesis, as suggested by the authors; these findings were later corroborated with findings of a similar study on the sea anemone Exaiptasia (Davy and Cook, 2001). In vivo carbon fixation by the symbiont is highly efficient in C. xamachana, with rates exceeding daily respiration requirements of the host, supporting a growth rate of 3% body weight per day (Verde and McCloskey, 1998;Welsh et al, 2009;Freeman et al, 2016). Contrary to carbon, nitrogen assimilation levels under both photosynthetic and non-photosynthetic conditions are low, suggesting alternative nitrogen sources are essential for life.…”
Section: Nutritional Requirementssupporting
confidence: 81%
See 1 more Smart Citation
“…These experiments showed that labeled glycerol disappeared in <30 min, likely through utilization in lipid synthesis, as suggested by the authors; these findings were later corroborated with findings of a similar study on the sea anemone Exaiptasia (Davy and Cook, 2001). In vivo carbon fixation by the symbiont is highly efficient in C. xamachana, with rates exceeding daily respiration requirements of the host, supporting a growth rate of 3% body weight per day (Verde and McCloskey, 1998;Welsh et al, 2009;Freeman et al, 2016). Contrary to carbon, nitrogen assimilation levels under both photosynthetic and non-photosynthetic conditions are low, suggesting alternative nitrogen sources are essential for life.…”
Section: Nutritional Requirementssupporting
confidence: 81%
“…High light penetrance is important for species within this genus, as the jellyfish hosts one or more photosynthetic dinoflagellate species of the genus Symbiodinium (Hofmann et al, 1996;Lampert, 2016). Similar to their coral relatives, nutrient exchange is a key component supporting this cnidarian-dinoflagellate mutualism (Hofmann and Kremer, 1981;Welsh et al, 2009;Freeman et al, 2016). In addition, Cassiopea spp.…”
Section: Introductionmentioning
confidence: 99%
“…Cyanobacteria are mostly associated with marine sponges and diatoms (see reviews by Freeman & Thacker, 2011;Foster et al, 2011;Venn et al, 2008), although they are also symbionts of haptophytes or dinoflagellates . Overall, for all these photosynthetic symbioses, light is of prime importance because it is needed by the symbionts as an energy source to fix inorganic carbon into organic compounds called photosynthates, most of which are transferred to the host for its own use (Freeman et al, 2016). Algae, such as dinoflagellates of the genus Symbiodinium, are associated with benthic animals such as reef-building corals, sea anemones, tridacnid molluscs, jellyfish (Cassiopea sp.…”
Section: Main Marine Symb I Os E S S Tud Ied Us Ing S Tab Le Isotope Smentioning
confidence: 99%
“…Algae, such as dinoflagellates of the genus Symbiodinium, are associated with benthic animals such as reef-building corals, sea anemones, tridacnid molluscs, jellyfish (Cassiopea sp. ), and foraminifera (Freeman, Stoner, Easson, Matterson, & Baker, 2016;Sachs & Wilcox, 2006;Venn et al, 2008). In the pelagic environment, photosymbiotic interactions also exist between microalgae and other protists (radiolarian, foraminifera) or metazoans (ciliates, dinoflagellates), although the exact nature of this partnership is often not formally demonstrated.…”
Section: Main Marine Symb I Os E S S Tud Ied Us Ing S Tab Le Isotope Smentioning
confidence: 99%
See 1 more Smart Citation